Green Phellodendri Chinensis Cortex-based carbon dots for ameliorating imiquimod-induced psoriasis-like inflammation in mice - Zhang, Meiling; Cheng, Jinjun; Hu, Jie; Luo, Juan; Zhang, Yue; Lu, Fang; Kong, Hui; Qu, Huihua; Zhao, Yan (Journal of nanobiotechnology, 2021)
Background Carbon dots (CDs) with multifaceted advantages have provided hope for development brand-new nanodrug for treating thorny diseases. This study developed a green and simple calcination method to prepare novel CDs as promising drug for psoriasis treatment. The as-prepared CDs using Phellodendri Chinensis Cortex (PCC) as sole precursor were characterized by a series of methods, mainly including electron microscopy, optical technology and X-ray photoelectron spectroscopy (XPS). Results Results displayed that fluorescence (Quantum yield = 5.63%) and nontoxic PCC-based CDs (PCC-CDs) with abundant chemical groups exhibited solubility and tiny sizes at average of (1.93 ± 0.53) nm, which may be beneficial for its inherent biological activity. Moreover, by using the typical imiquimod (IMQ)-induced psoriasis-like skin mouse model, we firstly demonstrated the pronounced anti-psoriasis activity of as-prepared PCC-CDs on ameliorating the appearance, psoriasis area and severity index (PASI) scores as well as histopathological morphology of both back skin tissues and right ears in IMQ-induced mouse. Further potential mechanisms behind the anti-psoriasis activities may be related to suppress M1 polarization and relatively promote M2 polarization of macrophage both in vitro and in vivo. Conclusion These results suggested that PCC-CDs have potential to be an anti-psoriasis candidate for clinical applications to treat psoriasis, which not only provided an evidence for further broadening the biological application of CDs, but also provided a potential hope for application nanodrugs to treat thorny diseases. Graphic Abstract